The Entrepreneurship Role of Freelancers - Theory with Evidence from the Construction Industry - Burke, Andrew (Senate Hall, 2011)
In the entrepreneurship literature freelance workers are often categorised as a small and underperforming version of entrepreneurial owner managers. By contrast, in the industrial relations literature they are often depicted as a form of exploited worker. In this paper we explore the overlooked contextual entrepreneurial function of freelancers where they are the enablers of entrepreneurship rather than the entrepreneurial agents themselves. We outline some key hypotheses and test them in the construction industry where freelancers supply routine labour. We show that freelancers play a key role in their own right in enabling entrepreneurial performance by facilitating the use of de-risking strategies, reducing financial constraints, increasing entrepreneurial strategic agility as well as facilitating market entry by start-ups. This paper is a first but important step towards facilitating a new research trajectory focusing on the contextual role of freelancers in the entrepreneurial economy. Keywords: freelance, entrepreneur, contextualizing entrepreneurship, construction industry
Keywords: freelance|entrepreneur|contextualizing entrepreneurship|construction industry